Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis. Issue 2 (April 2023) - Yan, Ling; Guo, Weijuan; Huang, Binbin; Chen, Yujun; Ren, Xinyu; Shen, Yiyang; Zhou, Yefeng; Cheng, Rui; Zhang, Jie; Qiu, Muqing; Hu, Baowei
Abstract: Cr(VI) contained the characteristic of water solubility, mobility and cell permeability in aqueous solution. As a result, the treatment of Cr(VI) in aqueous solution was very necessary before it was discharged into water body. A novel adsorbent of the modified biochar with chitosan schiff base and MnFe2 O4 nanoparticles (CsSB/MnFe2 O4 @BC) was prepared, characterized and applied into the elimination of Cr(VI) by batch adsorption process. CsSB/MnFe2 O4 @BC composites were characterized by some technologies (Such as SEM, TEM, XRD and FT-IR). The results showed that it was an irregular, wavy and heterogeneous surface, and it contained MnFe2 O4 nanoparticles and functional groups of C − H, O − H and C − O − C stretching vibrations. The operational parameters (For example, pH, concentration of Cr(VI), contact time and temperature) had an important influence on the adsorption capacity of Cr(VI) removal. The adsorption processes were best fitted to Pseudo-second order model and Freundlich model. Additionally, the maximum uptake capacity of Cr(VI) ions reached 125.34 mg/g. The possible mechanisms were ion exchange, surface complexation, electrostatic attraction, and pore adsorption. After five cycles, adsorption capacity of Cr(VI) by CsSB/MnFe2 O4 @BC still remained high, and reached 102.45 mg/g. Therefore, it was a simple, economical, efficiency and reuse adsorbent and could be used as an high efficient adsorbent in the treatment of Cr(VI) in aqueous solution. Highlights: CsSB/MnFe2 O4 @BC was prepared, characterized and applied for Cr(VI) removal. It was a simple, economical, efficiency and reuse adsorbent. Mechanism was elaborated in details.